Implementation of Child Protection Implementation, Somba Opu District, Gowa Regency - M. Awaluddin (Universitas Negeri Makassar, 2022)
In essence, the child is unable to protect himself from various kinds that cause mental, physical, social losses in various areas of life and livelihood . This study aims to determine the Implementation of Child Protection in Somba Opu District. The research method used is a qualitative method to see the relationship between variables. Data collection techniques use interviews, and documentation. The data analysis technique uses several steps according to the theory of Miles, Hubermas and Saldana, namely analyzing the data with three steps: condensing the data, presenting the data, and drawing conclusions or verification. The results of the study based on interviews and observations show that the implementation is not efficient and effective in terms of human resources where the resources in Edwards III theory are one of the indicators that the implementation is efficient and effective, therefore Regional Regulation Number 5 of 2014 according to article 4 letter a on prevention has not been maximized because the Office of Women's Empowerment and Child Protection still requires a large number of human resources. If, in terms of communication indicators, the disposition and bureaucratic structure in Edwards III's theory is said to be effective and efficient implementation because it is interrelated and works as it should.